Nonlinear Approaches in Engineering Application Design Engineering Problems - Dai, Liming; Jazar, Reza N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Nonlinear Approaches in Engineering Applications: Design Engineering Problems examines the latest applications of nonlinear approaches in engineering and addresses a range of scientific problems. Chapters are authored by world-class scientists and researchers and focus on the application of nonlinear approaches in different disciplines of engineering and scientific applications, with a strong emphasis on application, physical meaning, and methodologies of the approaches. Topics covered are of high interest in engineering and physics, and an attempt has been made to expose engineers and researchers to a broad range of practical topics and approaches. This book is appropriate for researchers, students, and practicing engineers who are interested in the applications of engineering, physics, and mathematics in nonlinear approaches to solving engineering and science problems. Presents a broad range of practical topics and approaches; Explains approaches to better, safer, and cheaper systems; Emphasizes applications, physical meaning, and methodologies. .
Improved Theoretical and Numerical Approaches for Solving Linear and Nonlinear Dynamic Systems -- Nonlinear Aspects of Space Charge Phenomena -- Real-time Nonlinear Model Predictive Control Optimizers for Adaptive Cruise Control: A Comparative Study -- Kinematics Once Again -- A New Strategy for Form-finding and Optimal Design of Space Cable Network Structures -- Maximizing Occupant Thermal Comfort by Using Game Theory -- Wind Resource Assessment -- Roll Model Control of Autonomous Vehicle -- Roll Model Control of Autonomous Vehicle -- Influence of Lateral Asymmetry on Car's Lateral Dynamics -- Vehicle Vibrations Analysis of the Quarter-car Model Considering Tire-road Separation -- Influence of Different Seating and Crank Positions on Kinematics and Muscular Activity in Elite Handcycling.
Keywords: Dynamics; Nonlinear theories; Control engineering; System theory; Automotive engineering; Multibody systems; Vibration; Mechanics, Applied; Applied Dynamical Systems; Control and Systems Theory; Complex Systems; Automotive Engineering; Multibody Systems and Mechanical Vibrations; Engineering mathematics; Nonlinear theories